SELF MANAGEMENT CONCEPT DALAM KEPEMIMPINAN LEMBAGA PENDIDIKAN - SYAMSURIADI Syamsuriadi (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract. Self-management concept is a leadership concept needed by leaders in educational institutions. In this context, self-management concept directs a leader of an educational institution to change attitudes, improve self-image, continue to work and work, maintain physical health, improve mind power, develop spiritual life, do things now, be consistent in learning, develop networks, build and maintain relationships, develop others by developing reasons why it is necessary to build others, empower others and create leaders, and build groups to grow together so as to ensure a conducive climate in educational institutions.